EKSISTENSI HUKUM ADAT ENDE LIO DALAM KASUS PERKAWINAN PARU DHEKO (KAWIN LARI) PADA MASYARAKAT DESA EMBUZOZO, KECAMATAN NANGAPANDA, KABUPATEN ENDE - Petu, Modestus Angrianus; Hedewata, Agustinus; Mauritsius, Darius (Law Faculty, Nusa Cendana University, 2023)
The objectives of this study are: (1) to determine the factors behind and the negative impacts arising from paru dheko marriage (eloping) on the community of Embuzozo Village, Nangapanda District, Ende Regency. (2) To know the process of completing paru dheko marriage (eloping) according to the customary law of Ende Lio. This research is an empirical juridical research with data collection techniques, observation and interviews of 13 respondents, and documentation. The data were analyzed in a qualitative descriptive manner. The factors behind the occurrence of paru dheko marriage (eloping) are factors of pregnancy out of wedlock, not approved by parents and fear of no accountability from the man, the negative impact arising from paru dheko marriage (eloping) is to be the subject of ridicule causing conflict between two big families, causing self-esteem, and family self-esteem falling, humiliating yourself, family, traditional leaders and even communities, communities become the subject of ridicule from other communities, and become magnets for other unmarried couples and The process of settling paru dheko marriage (eloping) according to the customary law of ende lio as follows; Ende Lio customary law, especially in the Tanazozo area, Embuzozo Village still prioritizes the principle of harmony and peace by resolving it through the customary process, of course, the purchase is inseparable. Indigenous leaders play a major role in the process of completing paru dheko (eloping) marriage